Resilience of Alpha Generation: Digital Resiliency, Organizational Culture, and Talent Management - Maharani, Haidilia; Amaliah, Ima; Nurhayati, Nunung (Publisher Cv. Inara, 2026)
Digital transformation and changes in global work dynamics are driving the emergence of Generation Alpha as a future workforce group with digital-native characteristics, visual orientation, and high expectations for flexibility and value alignment. These conditions demand a new understanding of work resilience that relies on structural stability and sustainable adaptability. This study aims to examine the influence of digital readiness, organizational culture, and talent management strategies on the resilience of Generation Alpha in the workplace. The method used is a qualitative literature study by analyzing reputable scientific articles that discuss work resilience, digital transformation, organizational culture, and talent management across organizational contexts. The results of the synthesis show that digital readiness plays a role as a foundation for resilience through strengthening self-efficacy, adaptive learning, and psychological resilience, although it has the potential to pose a risk of self-regulation if not balanced by organizational support. An adaptive, ethical, and learning-oriented organizational culture has been proven to strengthen the psychological safety and work attachment of Generation Alpha. Flexible and nonlinear talent management strategies become an institutional instrument to convert adaptive potential into long-term resilience. This study contributes to the development of the Alpha Generation resilience conceptual framework and provides practical implications for organizations in designing sustainable human resource strategies in the digital age of work.